Processo de Acreção em Estrelas T Tauri Clássicas do Aglomerado NGC 2264 - Alana Paixao de Sousa (2016)
NGC 2264 is a young stellar cluster ( 3 Myr) with hundreds of classical T Tauri stars (CTTSs) that allow us a detailed analysis of the accretion process taking place in these systems. NGC 2264 was target of a multiwavelength observational campaign in 2011 with CoRoT, MOST, Spitzer, and Chandra satellites. We also obtained spectroscopic data from the VLT (ESO) telescope equipped with the FLAMES spectrograph, among other observations from the ground. We classied the CoRoT light curves of CTTSs as spot-like, AA Tau, or aperiodic what includes the stars with variability due to accretion burst. We compared our classication to several accretion diagnostics (H and HeI (6678A) emission, UV excess), and disk (IR excess) parameters. We veried that accreting and non-accreting systems represent very distinctive groups with respect to UV excess, H emission and mass accretion rate. We showed that the morphology of the CoRoT light curve reects the evolution of the accretion process and of the inner disk region. Accretion burst light curves present high mass accretion rates and optically thick inner disks. The AA Tau-like systems, whose light curves are dominated by circumstellar dust obscuration, show intermediate mass accretion rates and are located in the transition of thick to anemic disks. CTTSs with spot-like light curves correspond mostly to low mass accretion rate, low near-IR excess systems. About 30% of the CTTSs observed in the 2008 and 2011 CoRoT runs changed their light-curve morphology. Transitions from AA Tau-like and spot-like to aperiodic light curves and vice versa were common. This shows that the circumstellar environment of young low mass stars is extremely dynamic on a timescale of a few years. The analysis of the H emission line variability of 58 accreting stars showed that 8 presented a periodicity that, in a few cases, was coincident with the photometric period. We also analysed the HeI (6678A ) line, formed near the hot spot and that, when periodic, provides a realistic estimate of the rotation period of the star. The analysis of the correlation observed accross the H line shows that the blue and red wings of the H line proles often do not present correlated variability with each other, indicating that they are inuenced by dierent physical processes, such as outows and accretion. We tested in our sample of stars the theoretical predictions of accretion in stable and unstable regimes, analysing the occurrence of redshifted absorption in the H line. Only 10 stars in our sample presented redshifted absorption, and among those we found only one star in the unstable accretion regime. The other stars in this small sample are apparently in a stable accretion regime, and this accretion regime agrees with the photometric variability found for these stars. However, the periodicity of the H line expected in the stable accretion regime is not always seen in our sample